Techniques and Instrumentation for Detection of Exoplanets II 2005
DOI: 10.1117/12.619140
|View full text |Cite
|
Sign up to set email alerts
|

Extreme adaptive optics testbed: high contrast measurements with a MEMS deformable mirror

Abstract: ABSTRACT"Extreme" adaptive optics systems are optimized for ultra-high-contrast applications, such as ground-based extrasolar planet detection. The Extreme Adaptive Optics Testbed at UC Santa Cruz is being used to investigate and develop technologies for high-contrast imaging, especially wavefront control. We use a simple optical design to minimize wavefront error and maximize the experimentally achievable contrast. A phase shifting diffraction interferometer (PSDI) measures wavefront errors with sub-nm precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…9 Earlier work with the MEMS device has been previously presented. [10][11][12][13] Here we discuss our flattening procedure and our latest and best contrast results with our MEMS.…”
Section: Introductionmentioning
confidence: 95%
“…9 Earlier work with the MEMS device has been previously presented. [10][11][12][13] Here we discuss our flattening procedure and our latest and best contrast results with our MEMS.…”
Section: Introductionmentioning
confidence: 95%
“…Control accuracy of a DM was demonstrated to a level of λ/10 000 rms (e.g. Brown et al 2003;Evans et al 2005), while some commercial wavefront sensors were reported to achieve absolute wavefront measurement accuracies of λ/1000 rms by the conventional Shack-Hartmann method (e.g. HASO HP 26 from Imagine Optic).…”
Section: Introductionmentioning
confidence: 99%
“…In imaging mode, the reference pinhole is replaced with a CCD camera and only the probe beam is used. Further information about contrast measurements can be found in prior works [26,63] and Chapter 4. In interferometry mode, the testbed becomes an extremely accurate optical metrology system.…”
Section: Description Of Exao Testbedmentioning
confidence: 99%
“…Errors in each of these tasks leads to errors in performance and these are summarized in an error budget. Preliminary work with the MEMS device, including some of the engineering challenges leading up to this result, have been presented in prior works [71,63,61]. A complete inventory of these difficulties, together with our mitigation techniques, is included here.…”
Section: Introductionmentioning
confidence: 99%